Straw Return and Nitrogen Fertilization to Maize Regulate Soil Properties, Microbial Community, and Enzyme Activities Under a Dual Cropping System - Yang, Li; Muhammad, Ihsan; Chi, Yu Xin; Wang, Dan; Zhou, Xun Bo (Frontiers in Microbiology, 2022)
Soil sustainability is based on soil microbial communities’ abundance and its composition. Straw returning (SR) and nitrogen (N) fertilization influence soil fertility, enzyme activities, and the soil microbial community and structure. However, still remain unclear due to heterogeneous composition and varying decomposition rate of added straw. Therefore, the current study aimed to determine the effect of SR and N fertilizer application on soil organic carbon (SOC), total nitrogen (TN), urease (S-UE) activity, sucrase (S-SC) activity, cellulose (S-CL) activity, bacterial, fungal and nematode community composition from March to December 2020 at Guangxi University, China. Treatments included two planting patterns that is SR and traditional planting (TP) and six N fertilizer with 0, 100, 150, 200, 250 and 300 kg N ha-1. Straw returning significantly increased soil fertility, enzymatic activities, community diversity and composition of bacterial and fungal compared to TP. Nitrogen fertilizer application increased soil fertility and enzymes, decreased richness of bacterial and fungal. In SR added plots, the dominated bacterial phyla were Proteobacteria, Acidobacterioia, Nitrospirae, Chloroflexi and Actinobacteriota; whereas fungal phyla were Ascomycota and Mortierellomycota and nematode genera were Pratylenchus and Acrobeloides. Co-occurrence network and Redundancy Analysis (RDA) analysis showed that TN, SOC and S-SC were closely correlated with bacterial community composition. It was concluded that the continuous SR and N fertilizer improved soil fertility and improved soil bacterial, fungal and nematode community composition.